A cross-sectional survey of nutrition labelling use and its associated factors on parents of school students in Shanghai, China - Ma, Jianhong; Zhu, Zhenxin; Chen, Xiao; Guo, Yan; Zhang, Huansheng; Zhang, Yuyan; Zang, Jiajie (Public health nutrition, 2018)
To understand parents' knowledge and use of nutrition labelling and to explore its associated factors. Cross-sectional survey. Two schools providing a nine-year educational programme in Putuo District, Shanghai, China, were selected for the study. Information was included on demographic data and knowledge of the Chinese Food Pagoda. Students and their parents (n 1770) participated in a questionnaire survey. Of questionnaires, 1766 were completed (response rate 99·8 %). Utilization rate of nutrition labelling was 19·3 %. Among 624 parents knowing nutrition labelling, 22·1 % understood all the information included, 70·7 % understood it partially and 7·2 % could not understand it at all. Use of nutrition labelling by parents was related to the following factors (OR; 95 % CI): high educational level of parent (1·465; 1·165, 1·841), parent's knowledge of the Chinese Food Pagoda (1·333; 1·053, 1·688), parent's consumption of top three snacks which are unhealthy (1·065; 1·023, 1·109), parent's assumption that nutrition labelling would affect their choice of food (1·522; 1·131, 2·048), student's willingness to learn about labels (1·449; 1·093, 1·920) and student's knowledge and use of labels (2·214; 1·951, 2·513). Parents' knowledge and use of nutrition labelling are still at a lower level, and some information included in the nutrition labels is not understood by parents. The forms of the existing nutrition labelling need to be continuously improved to facilitate their understanding and usefulness. It is necessary to establish nutrition projects focusing on education and use of nutrition labels which help parents and their children make the right choices in selecting foods.